vac2: a yeast mutant which distinguishes vacuole segregation from Golgi-to-vacuole protein targeting. - Shaw, J M (1991)
We have isolated four yeast mutants that are unable to partition maternal vacuoles into growing buds. Three of these vacuole segregation (vac) mutants also mislocalize the vacuolar protease carboxypeptidase Y (CPY) to the cell surface, a phenotype previously reported for vac strains. A fourth mutant, vac2-1, exhibits a temperature-sensitive defect in vacuole segregation but does not show a defect in protein targeting from the Golgi apparatus to the vacuole. Haploid vac2-1 cells grown at the non-permissive temperature do not secrete CPY or a second vacuolar protease, proteinase A (PrA). Furthermore, newly synthesized precursors of CPY are converted to mature forms with similar kinetics in both vac2-1 and wild-type cells. In addition, invertase is secreted normally from vac2-1 cells, indicating that post-Golgi steps in the secretory pathway are not blocked in this mutant. These results suggest that VAC2 function is necessary for vacuole division and segregation in yeast but is not involved in vacuole protein sorting events at the Golgi apparatus.